Ozone for Microalgae Biomass Harvesting from Wastewater. (4th July 2017) - Orta Ledesma de Velásquez, María Teresa; Monje-Ramírez, Ignacio; Velasquez-Orta, Sharon; Rodriguez-Muñiz, Verónica; Yáñez-Noguez, Isaura
ABSTRACT: The use of ozone has been investigated as a harvesting technique (ozone-flotation) for microalgae recovery from wastewater. This document summarizes the most outstanding results achieved to date by our working group, including the ozone effect on the lipid and fatty acid methyl ester (FAME) content. Additionally, the effect of the initial concentration of microalgal biomass on ozone-flotation was investigated using microalgae Scenedesmus sp. cultured in wastewater. Ozone-flotation required specific conditions to separate biomass from wastewater, depending on the type of microalgae strain, culture (single or mixed) and concentration. The effect of ozone-treatment improved lipid extractability and increased degree of FAME saturation.